Effect of Lower Versus Higher Red Meat Intake on Cardiometabolic and Cancer Outcomes A Systematic Review of Randomized Trials - Zeraatkar, Dena; Johnston, Bradley C.; Bartoszko, Jessica; Cheung, Kevin; Bala, Malgorzata M.; Valli, Claudia; Rabassa, Montserrat; Sit, Daegen; Milio, Kirolos; Sadeghirad, Behnam; Agarwal, Arnav; Zea, Adriana M.; et al. (Amer Coll Physicians, 2019)
Background: Few randomized trials have evaluated the effect of reducing red meat intake on clinically important outcomes. Purpose: To summarize the effect of lower versus higher red meat intake on the incidence of cardiometabolic and cancer outcomes in adults. Data Sources: EMBASE, CENTRAL, CINAHL, Web of Science, and ProQuest from inception to July 2018 and MEDLINE from inception to April 2019, without language restrictions. Study Selection: Randomized trials (published in any language) comparing diets lower in red meat with diets higher in red meat that differed by a gradient of at least 1 serving per week for 6 months or more. Data Extraction: Teams of 2 reviewers independently extracted data and assessed the risk of bias and the certainty of the evidence. Data Synthesis: Of 12 eligible trials, a single trial enrolling 48 835 women provided the most credible, though still low-certainty, evidence that diets lower in red meat may have little or no effect on all-cause mortality (hazard ratio [HR], 0.99 [95% CI, 0.95 to 1.03]), cardiovascular mortality (HR, 0.98 [CI, 0.91 to 1.06]), and cardiovascular disease (HR, 0.99 [CI, 0.94 to 1.05]). That trial also provided low- to very-low-certainty evidence that diets lower in red meat may have little or no effect on total cancer mortality (HR, 0.95 [CI, 0.89 to 1.01]) and the incidence of cancer, including colorectal cancer (HR, 1.04 [CI, 0.90 to 1.20]) and breast cancer (HR, 0.97 [0.90 to 1.04]). Limitations: There were few trials, most addressing only surrogate outcomes, with heterogeneous comparators and small gradients in red meat consumption between lower versus higher intake groups. Conclusion: Low- to very-low-certainty evidence suggests that diets restricted in red meat may have little or no effect on major cardiometabolic outcomes and cancer mortality and incidence. Primary Funding Source: None (PROSPERO: CRD42017074074).